Balechina and the new genus Cucumeridinium gen. nov. (Dinophyceae), unarmored dinoflagellates with thick cell coverings. Issue 6 (19th October 2015) - Gómez, Fernando; López‐García, Purificación; Takayama, Haruyoshi; Moreira, David
Abstract : The genus Balechina (=subgenus Pachydinium ) was established for heterotrophic gymnodinioid dinoflagellates with a thick cell covering. The type species, B. pachydermata (= Gymnodinium pachyderm‐atum ), showed numerous fine longitudinal striae, whereas B. coerulea (= G. coeruleum ) showed 24 prominent longitudinal surface ridges or furrows and a distinctive blue pigmentation. We have investigated the morphology and molecular phylogeny of these taxa and the species Gymnodinium cucumis, G. lira and G. amphora from the western Mediterranean, Brazil and Japan. Sudden contractions at the cingulum level were seen in B. pachydermata, which also showed a high morphological variability which included morphotypes that have been described as Amphidinium vasculum, G. amphora, G. dogielii and G. gracile sensu Kofoid and Swezy. Molecular phylogeny based on small subunit rRNA gene sequences revealed that Balechina coerulea, G. cucumis and G. lira formed a clade distantly related to the clade of the type species, B. pachydermata, and G. amphora . We propose the new genus Cucumeridinium for the species with longitudinal ridges and a circular apical groove ( Cucumeridinium coeruleum comb. nov., C. lira comb. nov. and C. cucumis comb. nov.), and Gymnodinium canus and G. costatum are considered synonyms of C. coeruleum . The genus Balechina remains for the species with a double‐layer cell covering, bossed surface with fine striae, and an elongated elliptical apical groove. At present, the genus is monotypic containing only B. pachydermata .